Old age and inequalities in Egypt. The role of intergenerational relationships and transfers within the family - Angeli, Aurora (2014)
The paper aims at analysing the condition of the elderly in Egypt, a country where ageing is a rising trend. Our focus is on the role intergenerational ties and transfers within the family have in alleviating poverty situations of aged people. We analyse old people living arrangements in order to underline the spread of vulnerability among them. In a social and economic context where old people are vulnerable to poverty, we intend to investigate the importance of economic and non-economic flows towards the elderly. We use individual data from Egypt Labour Market Survey 1998 and 2006 that inform about demographic characteristics of individuals, households, housing conditions and non-work sources of income.